Automotive Development Center (ADC): The hub of automotive Research & Development (R&D) in Universiti Teknologi Malaysia (UTM) - Azhar, Abdul Aziz, Assoc. Prof. Dr. Ir. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/